2012
DOI: 10.1371/journal.pone.0042868
|View full text |Cite
|
Sign up to set email alerts
|

Polyubiquitin Is Required for Growth, Development and Pathogenicity in the Rice Blast Fungus Magnaporthe oryzae

Abstract: Protein ubiquitination, which is highly selective, regulates many important biological processes including cellular differentiation and pathogenesis in eukaryotic cells. Here, we integrated pharmacological, molecular and proteomic approaches to explore the role of ubiquitination in Magnaporthe oryzae, the leading fungal disease of rice world-wide. Inhibition of ubiquitin-mediated proteolysis using the 26S proteasome inhibitor, Bortezomib, significantly attenuated conidia germination, appressorium formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…They are involved in the adaptation of metabolism by degrading transcriptional regulators (Hershko and Ciechanover 1998). Recent studies have demonstrated the relation between ubiquitin-mediated proteolysis, conidial germination and pathogenicity in M. oryzae (Oh et al 2012). In our study, the 26S proteasome nonATPase regulatory subunit 12 (spot 75) and proteasome A-type (spot 106) were identified in the conidial proteomes of both stages, but up-regulated in ungerminated conidia.…”
Section: Proteome Miningmentioning
confidence: 50%
“…They are involved in the adaptation of metabolism by degrading transcriptional regulators (Hershko and Ciechanover 1998). Recent studies have demonstrated the relation between ubiquitin-mediated proteolysis, conidial germination and pathogenicity in M. oryzae (Oh et al 2012). In our study, the 26S proteasome nonATPase regulatory subunit 12 (spot 75) and proteasome A-type (spot 106) were identified in the conidial proteomes of both stages, but up-regulated in ungerminated conidia.…”
Section: Proteome Miningmentioning
confidence: 50%
“…Unlike ubiquitination, SUMOylation does not involve protein degradation, but instead enhances protein stability (Müller et al ., ). A previous study on ubiquitination in M. oryzae identified SUMO, E1 and E2 enzymes as ubiquitination components using a domain search method (Oh et al ., ). However, SUMOylation and other PTMs in yeast utilize different machineries (Johnson et al ., ; Müller et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The whole infectious cycle of M. oryzae , from surface recognition, adherence, and appressorium formation to infectious growth and pathogenicity, is closely related to signal transduction pathways and protein degradation processes. The typical signal transduction pathways, including mitogen activated protein kinase (MAPK), cyclic adenosine monophosphate (cAMP), and calcium signal transduction pathways4567, and the protein degradation processes, including autophagy8910, ubiquitin mediated protein degradation111213 and calpains1415, have been confirmed to play significant roles in cell cycling, cellular differentiation and pathogenesis of M. oryzae .…”
mentioning
confidence: 99%